Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jp503886s
|View full text |Cite
|
Sign up to set email alerts
|

Facile Bioanchoring Strategy for the Preparation of Hierarchical Multiple Structured ZnO Crystals and Its Application as a Photoanode in Dye Sensitized Solar Cells

Abstract: This paper demonstrates a facile bioanchoring strategy for controlling the crystal growth process of ZnO crystals during calcination to form hierarchical multiple structures. Crystalline phase and morphology of ZnO was investigated using X-ray diffraction, scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. Results revealed the evolution of ZnO nanocrystallites from nanosize to hierarchical self-assembly of polydispersed microstructures of bars/sheets/spheres/hollow sph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Figure 2a shows the XRD patterns of ZnO, which exhibited sharp peaks at 2u ¼ 32, 34.4, 36.3, 47.5, 56.5, 62.9, 66.3, and 67.88. These peaks are assigned to the ZnO crystal structure with miller indices (100), (002), (101), (102), (110), (103), (200) (112), and (201) confirms the formation of ZnO in wurzite hexagonal phase [40]. Figure 2b shows the XRD pattern of PVK it exhibited two peaks at 2u ¼ 8 and 20.88 with d-spacing of 4.2, 10.8 Ar evealed face-to-face ordered structure of PVK [48].…”
Section: Ft-ir Spectroscopymentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 2a shows the XRD patterns of ZnO, which exhibited sharp peaks at 2u ¼ 32, 34.4, 36.3, 47.5, 56.5, 62.9, 66.3, and 67.88. These peaks are assigned to the ZnO crystal structure with miller indices (100), (002), (101), (102), (110), (103), (200) (112), and (201) confirms the formation of ZnO in wurzite hexagonal phase [40]. Figure 2b shows the XRD pattern of PVK it exhibited two peaks at 2u ¼ 8 and 20.88 with d-spacing of 4.2, 10.8 Ar evealed face-to-face ordered structure of PVK [48].…”
Section: Ft-ir Spectroscopymentioning
confidence: 89%
“…The solvent was evaporated under reduced pressure at 40 °C. Further, the prepared zinc oxide was calcined at 800 °C .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Albeit lithium batteries have a major dependence on the performance of electrodes, it is often demonstrated that electrolytes do limit the voltage window, charge transport, and conductivity and thereby the corresponding energy density, power density, and cycle life of the energy storage systems. [32][33][34] Also, we have recently studied the synthesis and liquid crystalline properties of ammonium and imidazolium-based ionic liquid crystalline materials derived from cardanol. But the leakage of volatile and toxic liquid electrolytes upon crimping the cell or during full paper domains and channels of 1D, 2D, and 3D ordered type are expected to facilitate the shuttling of Li + ions during charge and discharge process.…”
Section: Introductionmentioning
confidence: 99%
“…3‐pentadecyl phenol (cardanol), a commonly known biowaste from cashew nut shell processing industries is bestowed with the unique structure of long alkyl chain substituted phenol. Recently, we have reported several derivatives of this molecule, which were applied for the preparation of coatings, adhesives, liquid crystalline templates, and as dopants for the preparation of nanostructured conducting polymers . Also, we have recently studied the synthesis and liquid crystalline properties of ammonium and imidazolium‐based ionic liquid crystalline materials derived from cardanol .…”
Section: Introductionmentioning
confidence: 99%